The Measurement Of Performance Using The Balanced Score Card In Islamic Banking - Tri Wahyuni; Suwignyo Widagdo; Hamzah Fansuri Yusuf (ABM: International Journal of Administration, Business and Management, 2019)
This study aimed to analyze the extent to which performance of the PT. BPR Sinar Artha Wuluhan when measure d using the four perspectives of the Balanced Scorecard. The research was conducted on the company's performance in 2013-2014. The data used are primary data obtained from interviews with the resource persons and distributing questionnaires to the respondents as many as 130 respondents, ie 95 respondents and 35 respondents. This study also used secondary data obtained from various sources such as the internet, books, journals, theses, and others associated with this research. Data processing method using test data quality, the data validity test and reliability test data to test the questionnaire with the help of analysis tools SPSS version 20. The data processing also uses four perspectives of the Balanced Scorecard, the financial perspective using ROA, ROE and NPM. Customers use the perspective of customer acquisition, customer retention and customer satisfaction. Internal business perspective using indicators of innovation and operations. Learning and Growth perspective using a level employee productivity, employee retention and employee satisfaction. The results showed overall scores obtained by the performance of the company amounted to 46,9 % who expressed the company's performance is not good. However, there is increasing from year to year has increased its performance is quite good. Keywords: Performance Measurement, Balanced Score Card